Implementation of HONO into the chemistry-climate model CHASER (V4.0): roles in tropospheric chemistry - Ha, Phuc; Kanaya, Yugo; Taketani, Fumikazu; Andrés Hernández, Maria Dolores; Weyland, Benjamin; Pfeilsticker, Klaus; Sudo, Kengo (Geoscientific model development, 2023)
Nitrous acid (HONO) is an important atmospheric gas given its contribution to the cycles of NOx and HOx, but its role in global atmospheric photochemistry is not fully understood. This study implemented three pathways of HONO formation in the chemistry-climate model CHASER (MIROC-ESM) to explore three physical phenomena: gas-phase kinetic reactions (GRs), direct emission (EM), and heterogeneous reactions on cloud and aerosol particles (HRs). We evaluated the simulations by the atmospheric aircraft-based measurements from EMeRGe-Asia-2018 (Effect of Megacities on the Transport and Transformation of Pollutants on the Regional to Global Scales), ATom-1 (atmospheric tomography), observations from the ship R/V Mirai, EANET (Acid Deposition Monitoring Network in eastern Asia)/EMEP (European Monitoring and Evaluation Programme) ground-based stationary observations, and the OMI (Ozone Monitoring Instrument). We showed that the inclusion of the HONO chemistry in the modelling process reduced the model bias against the measurements for PM2.5, NO3-/HNO3, NO2, OH, HO2, O3, and CO, especially in the lower troposphere and the North Pacific (NP) region. - - We found that the retrieved global abundance of tropospheric HONO was 1.4 TgN. Of the three source pathways, HRs and EM contributed 63 % and 26 % to the net HONO production, respectively. We also observed that reactions on the aerosol surfaces contributed larger amounts of HONO (51 %) than those on the cloud surfaces (12 %). The model exhibited significant negative biases for daytime HONO in the Asian off-the-coast region, compared with the airborne measurements by EMeRGe-Asia-2018, indicating the existence of unknown daytime HONO sources. Strengthening of aerosol uptake of NO2 near the surface and in the middle troposphere, cloud uptake, and direct HONO emission were all potential yet-unknown HONO sources. The most promising daytime source for HONO found in this study was the combination of enhanced aerosol uptake of NO2 and surface-catalysed HNO3 photolysis (maxST+JANO3-B case), which could also remedy the model bias for NO2 and O3 during EMeRGe. We also found that the simulated HONO abundance and its impact on NOx-O3 chemistry were sensitive to the yield of the heterogeneous conversion of NO2 to HONO (vs. HNO3). - - Inclusion of HONO reduced global tropospheric NOx (NO + NO2) levels by 20.4 %, thereby weakening the tropospheric oxidizing capacity (OH, O3) occurring for NOx-deficit environments (remote regions and upper altitudes), which in turn increased CH4 lifetime (13 %) and tropospheric CO abundance (8 %). The calculated reduction effect on the global ozone level reduced the model overestimates for tropospheric column ozone against OMI spaceborne observations for a large portion of the North Hemisphere. HRs on the surfaces of cloud particles, which have been neglected in previous modelling studies, were the main drivers of these impacts. This effect was particularly salient for the substantial reductions of levels of OH (40 %-67 %) and O3 (30 %-45 %) in the NP region during summer, given the significant reduction of the NOx level (50 %-95 %). In contrast, HRs on aerosol surfaces in China (Beijing) enhanced OH and O3 winter mean levels by 600 %-1700 % and 10 %-33 %, respectively, with regards to their minima in winter. Furthermore, sensitivity simulations revealed that the heterogeneous formation of HONO from NO2 and heterogenous photolysis of HNO3 coincided in the real atmosphere. Nevertheless, the global effects calculated in the combined case (enhancing aerosol uptakes of NO2 and implementing heterogeneous photolysis of HNO3), which most captured the measured daytime HONO level, still reduced the global tropospheric oxidizing capacity. Overall, our findings suggest that a global model that does not consider HONO heterogeneous mechanisms (especially photochemical heterogeneous formations) may erroneously predict the effect of HONO in remote areas and polluted regions.